Niebezpieczeństwo wyrządzenia znacznej szkody majątkowej jako skutek przestępstwa bezszkodowej niegospodarności - Płońska, Anna (Wydawnictwo Uniwersytetu Wrocławskiego, 2017)
The essence of the criminal conduct described in Article 296 § 1a of Polish Penal Code is defined as causing the immediate danger of material damage caused by the perpetrator who deals with the financial matters or the economic activity of an individual, a legal person or an organizational unit without legal personality represented under a legal obligation, the decision of the appropriate authority or the contract, abuses the authority vested in him or her or fails to fulfill his or her duties. This article has been devoted to the analysis of the consequences of the crime of non-damage mismanagement, along with an indispensable indication of its critical systemic and dogmatic appraisals. And while the defects of analyzed regulation are justified, they should not prejudge the total depenalization of the crime of non-damage mismanagement.
Keywords: szkody materialne; nadużycie zaufania; niegospodarność; art. 296 § 1a Kodeksu karnego